Representations of Human Development and Inequalities in Brazil based on Atlas Brasil Indicators and Indexes - Alves, Lidiane Aparecida (Revista Nacional de Gerenciamento de Cidades, 2020)
This article aims to reflect on the indicators and indices of the Atlas of Human Development in Brazil - Atlas Brasil, as an instrument for the knowledge of reality. In order to achieve this objective, a bibliographical survey was carried out on the theme, covering the international and national scales, in addition to the information provided by Atlas Brasil. It is noteworthy that by making available to all citizens on an interactive platform, easy to access and understand, Atlas Brasil is an important instrument to be suitable for promotion and monitoring, from national to local scale, of human development in the country. Due to the autonomy of Brazilian municipalities to achieve their public policies / services, the knowledge of intra-municipal heterogeneities, which affect development, for example, on the scale of “neighborhoods”, is useful to intervene in priority areas more precisely. This is already possible for metropolitan regions, perhaps soon for all Brazilian municipalities. Furthermore, the importance of providing and using information is ratified to increase people’s choice and freedom to transform the reality in which they live.